A STUDY OF THE GOVERNMENT'S ROLE IN THE PUBLIC–PRIVATE PARTNERSHIP (PPP) MANAGEMENT SCHEME: A CASE STUDY OF THE SITINJAU LAUIK FLYOVER PROJECT THROUGH THE COLLABORATION BETWEEN THE DIRECTORATE GENERAL OF HIGHWAYS AND PT. HUTAMA PANORAMA SITINJAU LAUIK - Hasudungan Sinaga; Anthoni Veery Mardianta; Gina Cynthia Raphita Hasibuan (RADJA PUBLIKA, 2026)
This study aims to analyze the role of government in managing Public-Private Partnership (PPP) projects through a case study of the Sitinjau Lauik Flyover development in West Sumatra Province, Indonesia. The project represents one of the strategic infrastructure initiatives implemented to improve safety and traffic flow along the challenging transportation corridor connecting Padang City and Solok. Within the PPP framework, the government functions not only as the project owner but also as a regulator, facilitator, provider of support and guarantees, and supervisor throughout the entire project lifecycle. This study employs both qualitative and quantitative approaches to obtain a comprehensive understanding of project management dynamics. Qualitative data were collected through in-depth interviews with stakeholders involved in the project, while quantitative data were gathered through Likert-scale questionnaires and analyzed using descriptive statistics. The analysis focuses on four principal dimensions of the government's role, namely regulatory functions, facilitative functions, government support, and supervision. The findings indicate that the government plays a significant role in directing policies, providing fiscal and non-fiscal support, and ensuring inter-agency coordination in the implementation of PPP projects. Nevertheless, the study also identifies several challenges faced by the government, including suboptimal inter-agency coordination, complex land acquisition processes, technical implementation issues, and policy consistency concerns that affect project sustainability. The study concludes that the success of PPP projects is strongly influenced by the government's institutional capacity, the effectiveness of project governance, and the quality of policies that facilitate balanced partnerships between the public and private sectors. Therefore, strengthening institutional coordination, enhancing transparency, and improving supervisory mechanisms are essential factors for increasing the effectiveness of PPP project implementation in Indonesia.